Implementasi Network Automation Untuk Konfigurasi Jaringan Baru Dengan Netmiko - Donny Rahardika; Niki Ratama (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2021)
The internet is a necessity at this time, every activity we do every day always requires the internet starting from communicating, doing work, looking for information and other needs. PT. Maxindo Mitra Solusi is a company engaged in telecommunications (internet) services, installing network devices so that every customer can enjoy internet services. Each network device needs to be configured to be able to connect to the internet. Configuration of network devices is still done conventionally, where the device is configured one by one, it takes time and effort in advance of the risks that are usually done by humans.With the Network Development Life Cycle (NDLC) method to overcome the above problems. in the development of this system using the Python programming language and the use of the help of the Netmiko library. The testing system used is black box testing, white box testing and questionnaires.By using Network automation the installation of a new network becomes easier and faster. Network operators just need to run the program and each device will be configured automatically. More programs require relatively low resources and can reduce the risk of errors. Keywords : Internet, Network Development Life Cycle, Network Automation.